Thermal Sprayed Coatings and Their Tribological Performances
DOI: 10.4018/978-1-4666-7489-9.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mechanical Properties and the Abrasive Wear of Thermal Spray Coatings

Abstract: Thermal spray is a generic term used to define a group of coating processes used to apply both metallic and non-metallic coatings. These coatings are usually defined by their hardness, strength, porosity, roughness, and wear resistance. In this chapter, the authors turn their attention to the mechanical and tribological properties of thermal spray coatings. The individual phase plays a very important role in determining the performance of the coating. However, evaluating the mechanical and tribological propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Although the fourth and fifth chromia imprints indicated that the specimens are characterized by higher resistance than the titania coatings. Taking into consideration the first four specimens from each category, the titania coated specimens exhibit higher strength against the indentation loads [26]. Fig.…”
Section: Fatigue Resultsmentioning
confidence: 99%
“…Although the fourth and fifth chromia imprints indicated that the specimens are characterized by higher resistance than the titania coatings. Taking into consideration the first four specimens from each category, the titania coated specimens exhibit higher strength against the indentation loads [26]. Fig.…”
Section: Fatigue Resultsmentioning
confidence: 99%
“…Moreover, the value of critical load is insufficient to predict nature of bond strength and the mechanism of coating failure. 26 Therefore, the pull-off test would be the more authentic method to assess bond strength compared to scratch test considering the bio-mechanical forces applied on implants in vivo.…”
Section: Discussionmentioning
confidence: 99%